2018
DOI: 10.1007/s11064-018-2571-2
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Exercise Ameliorates Spatial Learning and Memory Deficits Through Improving the Clearance of Peripheral and Central Amyloid-Beta Levels

Abstract: Aggregated amyloid beta (Aβ) peptides are believed to play a decisive role in the pathology of Alzheimer's disease (AD). Previous evidence suggested that exercise contributes to the improvement of cognitive decline and slows down pathogenesis of AD; however, the exact mechanisms for this have not been fully understood. Here, we evaluated the effect of a 4-week moderate treadmill exercise on spatial memory via central and peripheral Aβ clearance mechanisms following developed AD-like neuropathology induced by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 75 publications
5
37
0
2
Order By: Relevance
“…This finding, however, does not align with meta-analytic research showing that exercise may have greater effects on memory function (not specifically face-name memory) for younger adults (vs. older adults) [39]. Lastly, although we observed null effects of acute exercise on face-name memory performance, which is a paired associative task, with such tasks involving hippocampal integration [50], animal work generally demonstrates that acute exercise can have profound effects on hippocampal neuronal activity [1] and hippocampal-dependent memory function [19,46].…”
Section: Discussionsupporting
confidence: 57%
“…This finding, however, does not align with meta-analytic research showing that exercise may have greater effects on memory function (not specifically face-name memory) for younger adults (vs. older adults) [39]. Lastly, although we observed null effects of acute exercise on face-name memory performance, which is a paired associative task, with such tasks involving hippocampal integration [50], animal work generally demonstrates that acute exercise can have profound effects on hippocampal neuronal activity [1] and hippocampal-dependent memory function [19,46].…”
Section: Discussionsupporting
confidence: 57%
“…On the one hand, exercise reduces the production of toxic amyloid-β peptides by inhibiting β-and γ-secretases that promote the liberation of amyloid-β from the amyloid precursor protein [19]. On the other hand, exercise can increase amyloid-β degrading enzymes [17], which may reduce the accumulation of amyloid plaques. In addition, exercise can promote the exchange of water and soluble contents between the cerebrospinal fluid and the interstitial fluid, which plays an important role in the clearance of amyloid plaques [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that exercise may promote neuroplasticity and play a neuroprotective role by affecting insulin-like growth factor-1, anti-inflammation and brain-derived neurotrophic factor pathways [11][12][13][14][15]. Additionally, exercise, especially resistance training, may affect the burden of amyloid plaques, which are associated with cognitive decline [16][17][18][19]. One study found that resistance training can directly decrease circulating insulin [20], of which an increase may affect the distribution of amyloid 40 and 42 in brain regions, resulting in the accumulation of amyloid plaques [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that healthy lifestyle improves mental activity and reduces the risk of various diseases . Indeed, it has been reported that nonpharmacological interventions improve neural repair and synaptic plasticity in the central nervous system (CNS) .…”
Section: Introductionmentioning
confidence: 99%